Evaluation of the Economic Efficiency of Radiology Units in Hospitals Affiliated with Shahid Sadoughi University of Medical Sciences, Yazd - Ebrahim Bahrami Nia; Reza Shams Allahi; Sedigheh GHolamrezaee; Mohamad mehdi Zare shahne (بیمارستان)
Background and purpose: Radiology departments are among the most critical units in hospitals due to their significant role in diagnosing and treating diseases. Given the high cost of radiology equipment and the revenue these departments generate, improving service delivery and enhancing efficiency are of paramount importance. This study aimed to evaluate the economic efficiency of radiology units in hospitals affiliated with Shahid Sadoughi University of Medical Sciences, Yazd. Methods: This descriptive-survey research was conducted as an applied study. Data on input and output variables were collected from nine hospitals under Shahid Sadoughi University of Medical Sciences. Input variables included the number of expert staff, the number of radiologists, the number of radiology devices, and the number of CT scan devices. Output variables comprised the number of admitted patients, the number of registered radiological images, and the total revenue generated. Results: The average technical and scale efficiency score was 0.910. Among the radiology units studied, 55% were found to be economically inefficient. Shahid Sadoughi Hospital exhibited decreasing returns to scale, while Shahid Beheshti Taft, Khatam al-Anbia Abarkouh, Waliasr (AS) Bafq, and Ziaei Ardakan hospitals showed increasing returns to scale. Additionally, Dr. Rahman, Afshar, Fatemeh Al-Zahra (S) Mehriz, and Imam Jafar Sadiq (AS) hospitals demonstrated constant returns to scale. Conclusion: Eliminating surplus manpower, based on the results of the Data Envelopment Analysis (DEA) method, plays a crucial role in reducing hospital and healthcare sector costs and enhancing hospital efficiency.